2018 21st International Conference on Intelligent Transportation Systems (ITSC) 2018
DOI: 10.1109/itsc.2018.8569437
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to the Citywide Traffic Accident Risk Prediction

Abstract: With the rapid development of urbanization, the boom of vehicle numbers has resulted in serious traffic accidents, which led to casualties and huge economic losses. The ability to predict the risk of traffic accident is important in the prevention of the occurrence of accidents and to reduce the damages caused by accidents in a proactive way. However, traffic accident risk prediction with high spatiotemporal resolution is difficult, mainly due to the complex traffic environment, human behavior, and lack of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(66 citation statements)
references
References 12 publications
0
65
0
1
Order By: Relevance
“…Hence, AI can capture the spatial-temporal pattern of accidents in databases and identify patterns for which mitigation strategies can be designed. For example, a study [85] used deep recurrent neural network approach to predict the risk of traffic accidents by analysing the spatial and temporal patterns from a traffic accident database in Beijing, China. The results showed that this method was effective and can be applied to warn people around hazardous locations.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Hence, AI can capture the spatial-temporal pattern of accidents in databases and identify patterns for which mitigation strategies can be designed. For example, a study [85] used deep recurrent neural network approach to predict the risk of traffic accidents by analysing the spatial and temporal patterns from a traffic accident database in Beijing, China. The results showed that this method was effective and can be applied to warn people around hazardous locations.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…For example, Chen et al (2016) have used a stack denoising AE (SDAE) to learn the hierarchical features of human mobility and their correlation with a traffic incident. In contrast, Ren et al (2017) and (Bao et al 2019) have implemented an LSTM model to evaluate risk, but Ren et al (2017) achieved better performance due to learning from more features.…”
Section: Traffic Incident Inferencementioning
confidence: 99%
“…Meanwhile, in Theofilatos's work [12], the idea of finite mixture logit models combined with Bayesian model was used to investigate accident likelihood and severity on urban arterials. Additionally, Ren et al [13] analyzed the spatial and temporal patterns of traffic accident frequency and proposed a deep learning approach to predict the risk of citywide traffic accident. Considering the spatial heterogeneity challenge in the data, the special deep learning method Hetero-ConvLSTM framework was proposed in work [14], which made reasonably accurate prediction results.…”
Section: Related Workmentioning
confidence: 99%